The scholarly communications cookbook - Buljung, Brianna; Bongiovanni, Emily (Association of College and Research Libraries, 2021)
The Scholarly Communications Cookbook features 84 recipes that can help you establish programs, teach concepts, conduct outreach, and use scholarly communications technologies in your library. The book is divided into 4 thorough sections. Recipes can be used by those new to scholarly communications, early-career librarians, and more experienced professionals looking for fresh ideas for their institution.